Association of serum procalcitonin level with acute respiratory distress syndrome in patients following cardiopulmonary bypass - Islam, Mohammad Azizul; Tamal, S. M. Taslim Yusuf; Samad, Abdus; Islam, Sadia; Karmokar, Shovon; Ghosh, Retina; Raju, Mezanur Rahman; Zafar-Al-Nimari, M.; Azim, Anowarul (International Surgery Journal, 2024)
Background: Acute respiratory distress syndrome is a potentially life-threatening complication after cardiac surgery. Systemic inflammatory response is activated during cardiopulmonary bypass time which may cause acute respiratory distress syndrome and serum procalcitonin level also increases during systemic inflammatory response. This study aimed to see the association of serum procalcitonin level with acute respiratory distress syndrome in patients following cardiopulmonary bypass. Methods: This was a prospective observational study conducted in the Department of Cardiac Surgery, National Heart Foundation Hospital and Research Institute, Dhaka, Bangladesh during the period from September, 2020 to August, 2022. In our study, we included 140 patients who underwent cardiac surgery with cardiopulmonary bypass. Patients were divided into two groups- group A included 70 patients with serum procalcitonin levels <7 ng/ml and group B included 70 patients with serum procalcitonin levels>7 ng/ml. Results: The mean (±SD) age of the patients was 43.20 (±13.18) years and 46.61 (±13.75) years in group A and group B respectively. In group A, 41.4% of patients were male and 58.6% were female; in group B, 52.9% were male and 47.1% were female. On 1st postoperative day, in group, A serum procalcitonin levels were 1.36(±0.97) ng/ml and in group B serum procalcitonin levels were 27.09(±26.11) ng/ml (p<0.001). The incidence of ARDS was significantly higher in group B than in group A (35.7% versus 8.5%, p= 0.002). Conclusion: This study concluded that there was an association of serum procalcitonin level with acute respiratory distress syndrome in patients following cardiopulmonary bypass.